2015
DOI: 10.1039/c5py00939a
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular glycopolymers with thermo-responsive self-assembly and lectin binding

Abstract: Incorporating monomers into sequence-defined synthetic macromolecules endows them to mimic nature which results in key residues being anchored in the molecular recognition pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…AP DMA-b-PNIPAM-b-PDMA triblock copolymer with adamantyl units in the PDMA block was utilized by Becer and co-workers. [111] Core-shell particles with radii of 120 nm were obtained above the LCST of the PNIPAM block. CDs or CDs with various mannose attachments were complexed with the adamantyl moieties to induce lectin binding,which led to smaller micelles with radii of 30 to 60 nm.…”
Section: Micelles/core-shell Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…AP DMA-b-PNIPAM-b-PDMA triblock copolymer with adamantyl units in the PDMA block was utilized by Becer and co-workers. [111] Core-shell particles with radii of 120 nm were obtained above the LCST of the PNIPAM block. CDs or CDs with various mannose attachments were complexed with the adamantyl moieties to induce lectin binding,which led to smaller micelles with radii of 30 to 60 nm.…”
Section: Micelles/core-shell Particlesmentioning
confidence: 99%
“…A β‐CD‐centered PLA 21‐arm star was grafted with POEGMA to obtain an amphiphilic block copolymer that formed micelles for delivery of DOX with a cmc of 3.1 mg L −1 and radii of 37 nm. A PDMA‐ b ‐PNIPAM‐ b ‐PDMA triblock copolymer with adamantyl units in the PDMA block was utilized by Becer and co‐workers . Core–shell particles with radii of 120 nm were obtained above the LCST of the PNIPAM block.…”
Section: The Tertiary Structure: Higher Order Assemblies Of Cd‐based mentioning
confidence: 99%
“…15,16 Furthermore, in order to promote the development of glyconanoparticles for different bio-related applications such as drug delivery, biomaterials, and biotechnologies it is necessary to understand the basis of selectivity and strength in the specific interactions between glycomaterials and lectins in more detail. [17][18][19][20][21][22] In general, there are two advanced synthesis strategies to prepare glycopolymers: either the direct polymerization of carbohydrate-bearing monomers or the synthesis of polymeric backbone bearing pendant reactive sites subsequently functionalized by carbohydrate moieties by using a combination of controlled/living polymerization techniques and click chemistry. 23 Cationic ring opening polymerization (CROP) is one of the earliest developed living polymerization techniques, but it has not been studied extensively yet for the preparation of glycopolymers due to the limited knowledge on direct polymerization of carbohydrate-containing cyclic monomers.…”
Section: Introductionmentioning
confidence: 99%
“…Bernard and Stenzel et al 65 reported the fabrication of comb-shaped supramolecular polymers via Ad-end-functionalized reversible addition-fragmentation chain transfer (RAFT) agent and b-CD-grafted polymers in aqueous media, and their reversible assembly was achieved by competing host analysis. Becer et al 66 prepared a thermoresponsive triblock copolymer by RAFT polymerization. This polymer could form inclusion complexes with mono-and hepta-mannosylated-CDs to further assemble into stable micelles (T 4 LCST (lower critical solution temperature)) covered with high carbohydrate density.…”
Section: Adamantyl Derivatives As Guests For the Construction Of Cd-dmentioning
confidence: 99%